Economy‐environment nexus for development: is Bangladesh on the right track? - Masukujjaman, Mohammad; Siwar, Chamhuri; Alam, A. S. A. Ferdous; Abdul Ghani, Ahmad Bashawir (Institute of Advanced Science Extension (IASE), 2016)
Economic growth has been a well-accepted method of development, reducing poverty until the urgency of human development comes into action.The sustainable development has been recognized as the most comprehensive concept for solving the socioeconomic and environmental problems in integration as both the growth and human development approaches are individually criticized enormously for being single centric.The purpose of the study is to diagnosis the growth, development and environmental status of Bangladesh and find out suitable development strategy based on sustainability paradigm.The present study is qualitative and exploratory in nature based on a case study method. Intensive desk research has been conducted based on the secondary data collected through various newspapers, magazines, published articles, and working papers via the internet.The study revealed that the development of Bangladesh is impressive for the last two decades coupled with epidemic levels of environmental degradation in the form of pollution, deforestation, land erosions and excessive natural resource endowments.The study concludes that it is a high time for Bangladesh to up-to-date their development strategy by adopting the sustainable development framework for the lasting growth and eco-friendly inclusive development.In doing so, specifically, Bangladesh should concentrate on creating green jobs in both the production and maintenance oriented sectors.